2002
DOI: 10.1051/apido:2001007
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Varroa destructor in South African honey bees: does cell space influence Varroa male survivorship?

Abstract: -The ability of Varroa destructor to reproduce in the African honey bee Apis mellifera scutellata was studied. In addition, the effects of space within the brood cell and short brood developmental time on mite reproduction, was investigated using A. m. scutellata cells parasitised by a A. m. capensis worker pseudo-clone. In A. m. scutellata worker cells Varroa produced 0.9 fertilised females per mother mite which is the same as found in susceptible European honey bees, but greater than the 0.4 produced in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 27 publications
5
52
1
4
Order By: Relevance
“…Even though most of the evidence obtained so far points towards Varroa mite tolerance in both sub-species of South Africa, Martin and Kryger (2002) found that Varroa mite reproductive rates were similar in A. m. scutellata and European honeybees, thereby suggesting that Varroa mites should have the same negative effect in A. m. scutellata as in European honeybees. Also, Martin and Kryger (2002) showed that Varroa mites were reproductively more successful in A. m. scutellata drone and worker cells compared to Africanised workers cells and that a higher percentage of fertile female mites were produced in A. m. scutellata compared to Africanised honeybees. Consequently, more studies are needed to give us a better idea of the reproductive potential of Varroa mites in both honeybee sub-species of South Africa and on the tolerance mechanisms that these honeybees developed against the parasite.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Even though most of the evidence obtained so far points towards Varroa mite tolerance in both sub-species of South Africa, Martin and Kryger (2002) found that Varroa mite reproductive rates were similar in A. m. scutellata and European honeybees, thereby suggesting that Varroa mites should have the same negative effect in A. m. scutellata as in European honeybees. Also, Martin and Kryger (2002) showed that Varroa mites were reproductively more successful in A. m. scutellata drone and worker cells compared to Africanised workers cells and that a higher percentage of fertile female mites were produced in A. m. scutellata compared to Africanised honeybees. Consequently, more studies are needed to give us a better idea of the reproductive potential of Varroa mites in both honeybee sub-species of South Africa and on the tolerance mechanisms that these honeybees developed against the parasite.…”
Section: Discussionmentioning
confidence: 84%
“…However, fertility rates can change over time, as was found in Brazilian honeybees where mite fertility was low before the late 1990's but increased after this period (Corrêa-Marques et al 2003;Garrido et al 2003;Carneiro et al 2007). Even though most of the evidence obtained so far points towards Varroa mite tolerance in both sub-species of South Africa, Martin and Kryger (2002) found that Varroa mite reproductive rates were similar in A. m. scutellata and European honeybees, thereby suggesting that Varroa mites should have the same negative effect in A. m. scutellata as in European honeybees. Also, Martin and Kryger (2002) showed that Varroa mites were reproductively more successful in A. m. scutellata drone and worker cells compared to Africanised workers cells and that a higher percentage of fertile female mites were produced in A. m. scutellata compared to Africanised honeybees.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…**Fecundity calculated in cells containing 3 or more offspring, to allow for a better comparison with Martin and Kryger (2002). ***Values as re-calculated by Martin and Kryger (2002). ****Only fertile foundresses were included in the fecundity assessment.…”
Section: Presence Of Deformed Drones and Workersmentioning
confidence: 99%